UTBK-SNBT Training and Information Provision for High School and Equivalent Students in Pekalongan - Arditya Prayogi; Riki Nasrullah (Journal of Sustainable Community Development, 2024)
Currently, the need for access to public tertiary institutions is important for high school students of the same level in Indonesia, including Pekalongan. Thus, the background of this service activity is carried out primarily to provide more detailed information related to the state university selection process in the form of test-based national selection (SNBP) - computer-based written exam (UTBK), as well as providing practice in the form of entrance exam questions. so that activity participants can better prepare themselves to take part in the selection. This is because, through state universities, high school/equivalent school students will get the opportunity to get quality education. Service activities are carried out using the main method of socialization and assistance in accessing information for state universities by collaborating with service partners from partners, in this case the tutoring party. From the service activities, it was found that the participants were enthusiastic in taking part in the activities as evidenced by good responses during the activities. Information and practice questions are provided so that participants can prepare themselves well for the state university entrance exam.